Analisis Yang Mempengaruhi Loyalitas Pelanggan SIM Card Telkomsel di Kota Padangsidimpuan - Ya’ti Ikhwani Nasution; Haidir Harianja (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to find out whether there is product quality, brand image and promotion on Telkomsel SIM CARD customer loyalty. This research is quantitative research and the analysis used is multiple regression analysis. The data collection technique used is a questionnaire method obtained directly from respondents, namely Telkomsel SIM CARD customers. Analyzed using statistical tools, namely SPSS Version 22. Based on the results of data processing, it shows that there is a significant partial and simultaneous influence between product quality, brand image and promotion variables on Telkomsel SIM CARD customer loyalty. For product quality variables, brand image and promotion have a positive effect on Telkomsel SIM CARD customer loyalty. The adjusted Rsquare value is 0.699. This means that 69.9% of the increase in Telkomsel SIM CARD customer loyalty can be explained by the independent variables, namely product quality, brand image and promotion. Meanwhile, 30.1% is explained by other factors.